Penglibatan dan Penilaian Pelajar Terhadap Sistem Penasihatan Akademik - Balkhais Jamaluddin; Siti Hasmiza Hassan; Siti Khairul Bariah Mohamood (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The Academic Advisory System (SPAk) serves as a profession towards the formation of knowledgeable, responsible, capable and competitive students in shaping students with superior personality. This study aims to analyze students' involvement and assessment of the Academic Advisory System at Polytechnic Sultan Abdul Halim Mu'adzam Shah (POLIMAS) during session 2 2022/2023 and session 1 2023/2024. Researchers have selected respondents among the students of the Department of Commerce which is 737 students for session 2 2022/2023 and 840 students for session 1 2023/2024 for this study. The study paper uses the Polytechnic Information Management System (SPMP) which is a platform to record various information related to students throughout the semester. The study on the effectiveness of the Academic Advisory System was conducted through the Academic Advisory Management (iPAd) menu found in SPMP. This study is a quantitative study that uses descriptive analysis to obtain frequency, percentage and mean values. The results of the study showed that the involvement of students in answering questions related to the role of academic advisors and the Academic Advisory System played an important role in the success of this study. The overall mean score value of academic advisory roles and the Academic Advisory System is above 3.70. In conclusion, the Academic Advisory System is indispensable in shaping students in terms of superior personality and excellent academics. This system is a systemic and structured service to connect students holistically and equip students with the knowledge, skills and values needed to make decisions related to education and career planning of students.